Dějiny premonstrátského kláštera v Milevsku: Milevský klášter od jeho založení po současnost - Tůmová, Petra (University of West Bohemia, 2022)
Diplomová práce se věnuje dějinám milevského premonstrátského kláštera od jeho založení mezi lety 1184-1187 do současnosti. Jejím cílem je podat ucelený pohled na jeho historický vývoj se zaměřením na posloupnost jeho představených a jejich činnost, která výrazně přispěla k rozkvětu kláštera ve 14. století. Současně se zabývá jeho majetkovým rozvojem. Soustředí se rovněž na období postupného úpadku kláštera za vlády tří světských rodů, které ovládaly panství do dvacátých let 17. století. Po bitvě na Bílé hoře se klášter dostal do správy kláštera strahovského, ve které zůstává dodnes.
Keywords: milevsko

Premonstrátský klášter a kostel sv. Jiljí v Milevsku - Zelenková, Pavla (Opera Facultatis theologiae catholicae Universitatis Carolinae Pragensis. Historia et historia artium, 2018)
Keywords: milevsko

Milevský klášter a jeho význam pro cestovní ruch Milevska - Houžvičková, Miroslava (Vysoká škola ekonomická v Praze, 2010)
The Premonstratensian monastery in Milevsko is the oldest monastery in South Bohemia and it belongs to the most valuable sights of the Czech Romanesque architecture. The aim of the bachelor thesis is to evaluate the importance of the monastery for the tourism of the town, to describe its potential and to provide enough information about this monument. This thesis also tries to analyse the position of this monastery in the town and the whole region and suggests eventual solutions to support the attendance of this monument.
Keywords: milevsko

Archeologický výzkum jádra premonstrátského kláštera v Milevsku (okr. Písek) - Břicháček, Pavel (Vladislav II., druhý král z Přemyslova rodu. K 850. výročí jeho korunovace, 2009)
Keywords: milevsko

Premonstrátský klášter Milevsko - Břicháček, Pavel; Kuchařová, Hedvika (Národní kulturní památka, 2009)
Keywords: milevsko

Nebe a peklo na zemi: románské a raně gotické dlaždice z milevského premonstrátského kláštera - Břicháček, Pavel (Vydalo Město Milevsko v Roce, 2007)
Keywords: milevsko

Jarloch a tzv. Ansbert, aneb, Nesmělá návštěva v tvůrčí dílně prvního milevského opata - Smékalová, Anna (Sborník prací Filozofické fakulty brněnské univerzity. C, Řada historická, 2006)
The theme of this partial study about the first abbot from Milevsko is only one element from the whole comlex of the problems pertinent to the historical conception of Gerlach, namely so called Ansbert alias the History about the crusade of the emperor Friedrich I. The editors of 19"1 century destroyed this conception of Gerlach because they ripped the complex of the texts included in the contemporary Strahov manuscript. We find the only version of the chronicle of Vincenc and Gerlach in this manuscript as well as the only complete text of the chronicle of so called Ansbert. Just this set represents the conception whole, parts of which cannot stand one without the others. The existence of the chronicle of so called Ansbert in the Strahov manuscript demonstrates Gerlach's larger scope than would be expected from the old editions. The likeliness of the fact that the manuscript was written in Milevsko is confirmed by the corrections in the text made by Gerlach himself. We have to suppose not only the existence of relatively furnish monastic scriptorium in Milevsko but also the contact of the Premonstratensian monastery in Milevsko with Cistercians in monastery Heiligenkreuz, from where the pattern for the copy of the History about the crusade of the emperor Friedrich I. in Strahov manuscript came. From this follows also the phase of preparation for writer activity of Gerlach, that means acquiring the patterns, copying them, finding out another annal sources and finally building up the conception and compiling the concept, according to what writers were able to copy. If we contemplate the historical activity of Gerlach as an insert of the History about the crusade of the emperor Friedrich I., or better, of his own work between the chronicle of Vincencius and the History and in the History, the conception of Gerlach comes into a magnificent light. We see not only an author who is trying to put all his sources together but also a creator of one great complex of texts that accords with the conception of writer activity of a medieval intellectual.
Keywords: milevsko

Patronáty milevského kláštera ve stredoveku - Adámek, Jan (Bibliotheca Strahoviensis, 2001)
[Die Patronatskirchen des Stiftes Mühlhausen im Mittelalter]
Keywords: milevsko

K osudům komunity milevského kláštera za husitských válek - Adámek, Jan (Táborský archiv, 1999)
[Schicksale des Prämonstratenserkonvents Mühlhausen während der Hussitenkriege]
Keywords: milevsko

Letopis milevského opata Jarlocha a jeho pramenná hodnota - Bláhová, Marie (Ceský stát na prelomu 12. a 13. století, 1993)
[Die Chronik des Abtes Jarloch von Mühlhausen und ihr Quellenwert. ]
Keywords: milevsko

Premonstratský klašter Milevsko - Dolista, Karel (Děkanský úřad, 1990)
[Das Prämonstratenserstift Mühlhausen]
Keywords: milevsko

Osm století milevského kláštera - Dolista, Karel (Duchovní pastýř, 1987)
The monastery in Milevsko - 800 years old
Keywords: milevsko

Premonstrátské opatství a kostel sv. Jiljí v Milevsku - Kuthan, Jiří (Umění: časopis Ústavu dějin umění Akademie věd České republiky, 1969)
[Prämonstratenserstift und -kirche St. Ägidius in Mühlhausen]
Keywords: milevsko

Kostel sv. Jiljí a premonstrátské opatství v Milevsko - Kuthan, Jiří (Jihočeský sborník historický, 1969)
St. Giles' Church and Premonstratensian Abbey in Milevsko
Keywords: milevsko